Development of Electronic Books (E-Books) for Supervision of Public Services to Increase Knowledge of PPKn Teachers (JED (Jurnal Etika Demokrasi), 2022)
People have the right to get good public services and can also participate in the supervision of it. Community rights in public services can be included in learning materials in schools. Knowledge about public service supervision for high school Civic Education teachers has not been maximized enough. The teachers should be at the forefront of socializing these rights by integrating them into Civics subject matter in Senior High School or Vocational High School (SMK). This study aimed to develop an e-book on public service supervision to increase high school and vocational high school teachers' knowledge. The research method was R&D (research and development) using Borgg and Gall theory. The study analyzed the need for enrichment book references for teachers to increase their knowledge about public service supervision. The results showed that the experts gave a good and proper assessment of this enrichment book. The effectiveness test showed that this enrichment book effectively increased the knowledge of Civic Education teachers on public services supervision. The benefit of this e-book is giving proper knowledge to Civic Education teachers in Senior High School (SMA) or Vocational High School (SMK) regarding the supervision of public services so that their knowledge can be increased.